Applicability of vital staining and tissue clearing to vascular anatomy and melanocytes' evaluation of temporal bone in six laboratory species. (27th March 2019) - Kim, Yoo Yeon; Chao, Janet Ren; Kim, Chulho; Kang, Tae‐Cheon; Park, Hae Sang; Chang, Jiwon; Suh, Jun‐Gyo; Lee, Jun Ho
Abstract: The purpose of the present study was to define the applicability of tissue clearing to the field of otology. We combined tissue clearing with vital staining perfusion via a pumping system to examine the vascular anatomy of temporal bones in laboratory animals. We used six different types of species including Korean wild mouse, mouse, Mongolian gerbil, hamsters and Guinea pigs. A mixture of Alcian blue reagent and 4% paraformaldehyde was circulated throughout the entire circulatory system of the animal via a perfusion pump system. Transparency images were obtained from the temporal bones according to the protocol of the SunHyun 3D Imaging Kit. In examining the inner surface of the tympanic membrane, flaccid part ( pars flaccida ) was positioned along the entire marginal area in Guinea pig. In the Guinea pig, unlike the other species, the cortical bone of the mastoid ( bullae ) was easily removed using cold instruments, allowing a direct approach to the enclosed structures. The distribution and pattern of cochlea melanocytes were compared among the species. "Mobius strip"‐like accumulated melanocytes in vestibules were shown in both the Korean wild mouse and mouse. The collateral blood supply to the cochlea in six different species was checked in various pattern. Combining dye infusion with tissue‐clearing techniques, we documented the middle ear and transparent inner ear structures in six different species. The information and associated images will help other researchers to develop hypotheses and design experimental investigations.